Perception and Production of Sentence Types by Inuktitut-English Bilinguals - Laura Colantoni; Gabrielle Klassen; Matthew Patience; Malina Radu; Olga Tararova (Languages, 2022)
We explore the perception and production of English statements, absolute yes-no questions, and declarative questions by Inuktitut-English sequential bilinguals. Inuktitut does not mark stress, and intonation is used as a cue for phrasing, while statements and questions are morphologically marked by a suffix added to the verbal root. Conversely, English absolute questions are both prosodically and syntactically marked, whereas the difference between statements and declarative questions is prosodic. To determine the degree of crosslinguistic influence (CLI) and whether CLI is more prevalent in tasks that require access to contextual information, bilinguals and controls performed three perception and two production tasks, with varying degrees of context. Results showed that bilinguals did not differ from controls in their perception of low-pass filtered utterances but diverged in contextualized tasks. In production, bilinguals, as opposed to controls, displayed a reduced use of pitch in the first pitch accent. In a discourse-completion task, they also diverged from controls in the number of non-target-like realizations, particularly in declarative question contexts. These findings demonstrate patterns of prosodic and morphosyntactic CLI and highlight the importance of incorporating contextual information in prosodic studies. Moreover, we show that the absence of tonal variations can be transferred in a stable language contact situation. Finally, the results indicate that comprehension may be hindered for this group of bilinguals when sentence type is not redundantly marked.